Performance evaluation of mobile ad hoc network in wireless LAN / Norfadhilah Hasan - Hasan, Norfadhilah (2005)
Mobile Ad-hoc Network (MANET) is becoming increasingly important in today's world and a number of protocols have been developed for them. However a comparison between them is lacking to help determine an optimal one. The work presented in this paper evaluates the performance of two MANET routing protocol known as Dynamic Source Routing (DSR) and Temporally Ordered Routing Algorithm (TORA). Simulation results are obtained with the aid of the OPNET Modeler, which is a commercial network simulation and evaluation tool. It discusses the effect of variation in number of nodes on protocol and assesses their relative performance. From the detailed simulation results and analysis of presented, an appropriate choice of routing protocol can be made for given network context and goal.